The small-secreted cysteine-rich protein CyrA is a virulence factor participating in the attack of Caenorhabditis elegans by Duddingtonia flagrans - Wernet, Nicole; Wernet, Valentin; Fischer, Reinhard (PLoS pathogens, 2021)
Nematode-trapping fungi (NTF) are a diverse and intriguing group of fungi that live saprotrophically but can switch to a predatory lifestyle when starving and in the presence of nematodes. NTF like Arthrobotrys oligospora or Duddingtonia flagrans produce adhesive trapping networks to catch and immobilize nematodes. After penetration of the cuticle, hyphae grow and develop inside the worm and secrete large amounts of hydrolytic enzymes for digestion. In many microbial pathogenic interactions small-secreted proteins (SSPs) are used to manipulate the host. The genome of D . flagrans encodes more than 100 of such putative SSPs one of which is the cy steine- r ich protein CyrA. We have chosen this gene for further analysis because it is only found in NTF and appeared to be upregulated during the interaction. We show that the cyrA gene was transcriptionally induced in trap cells, and the protein accumulated at the inner rim of the hyphal ring before Caenorhabditis elegans capture. After worm penetration, the protein appeared at the fungal infection bulb, where it is likely to be secreted with the help of the exocyst complex. A cyrA -deletion strain was less virulent, and the time from worm capture to paralysis was extended. Heterologous expression of CyrA in C . elegans reduced its lifespan. CyrA accumulated in C . elegans in coelomocytes where the protein possibly is inactivated. This is the first example that SSPs may be important in predatory microbial interactions.